2′-Fucosyllactose alters the composition and activity of gut microbiota from formula-fed infants receiving complementary feeding in a validated intestinal model. (October 2019) - Van den Abbeele, P.; Duysburgh, C.; Vazquez, E.; Chow, J.; Buck, R.; Marzorati, M.
Graphical abstract: Abstract: Human milk oligosaccharides are abundant in breast milk and are associated with various beneficial effects. In this study, a validated in vitro gut model was used to evaluate the prebiotic potential of 2′-fucosyllactose (2′-FL) on the activity and composition of microbiota from three 6-month-old formula-fed infants after weaning. 2′-FL was fermented along the entire length of the colon. In the distal colon, a specific decrease in lactate was observed accompanied with increased butyrate concentrations. 16S rRNA gene amplicon sequencing indicated shifts in the microbial composition at luminal and mucosal level, depending on donor and colon location. 2′-FL increased the relative abundance of Bifidobacterium adolescentis and of butyrate-producing bacteria, the latter only in the mucus. These data support the addition of 2′-FL to follow-on infant formulas and show that additional studies are needed to fully elucidate the mechanisms of action by which 2′-FL modulates the gut microbiota in older formula-fed infants.